2018
DOI: 10.1016/j.bcp.2018.10.017
|View full text |Cite|
|
Sign up to set email alerts
|

BRET-based assay to monitor EGFR transactivation by the AT1R reveals Gq/11 protein-independent activation and AT1R-EGFR complexes

Abstract: The type 1 angiotensin II (AngII) receptor (AT 1 R) transactivates the epidermal growth factor receptor (EGFR), which leads to pathological remodeling of heart, blood vessels and kidney. End-point assays are used as surrogates of EGFR activation, however these downstream readouts are not applicable to live cells, in real-time. Herein, we report the use of a bioluminescence resonance energy transfer (BRET)-based assay to assess recruitment of the EGFR adaptor protein, growth factor receptor-bound protein 2 (Grb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…In order to address this issue, we have developed the Receptor-Heteromer Investigation Technology (Receptor-HIT) [2,3], which has been used to investigate several G protein-coupled receptor (GPCR) heteromers [2,[4][5][6][7][8][9][10][11]. In addition, the Receptor-HIT assay has been used to characterize receptor tyrosine kinase (RTK) heteromers [12], as well as heteromers composed of both GPCRs and RTKs [13][14][15] or a GPCR and the Receptor for Advanced Glycation Endproducts [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address this issue, we have developed the Receptor-Heteromer Investigation Technology (Receptor-HIT) [2,3], which has been used to investigate several G protein-coupled receptor (GPCR) heteromers [2,[4][5][6][7][8][9][10][11]. In addition, the Receptor-HIT assay has been used to characterize receptor tyrosine kinase (RTK) heteromers [12], as well as heteromers composed of both GPCRs and RTKs [13][14][15] or a GPCR and the Receptor for Advanced Glycation Endproducts [16].…”
Section: Introductionmentioning
confidence: 99%
“…2021, 22, x 2 of 18 receptor (GPCR) heteromers [2,[4][5][6][7][8][9][10][11]. In addition, the Receptor-HIT assay has been used to characterize receptor tyrosine kinase (RTK) heteromers [12], as well as heteromers composed of both GPCRs and RTKs [13][14][15] or a GPCR and the Receptor for Advanced Glycation End-products [16]. The Receptor-HIT assay enables rapid identification, screening and profiling of receptor heteromers through ligand-dependent modulation of interactions between the receptors and specific biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Receptor-HIT has also been used to investigate heteromers composed of GPCRs and other receptors, including RTKs such as epidermal growth factor receptor (EGFR) [ 36 , 37 ], vascular endothelial growth factor receptor 2 (VEGFR2) [ 38 ], and the insulin receptor [ 39 ], as well as the receptor for advanced glycation end-products (RAGE) [ 40 ].…”
Section: Gpcr-other Receptor Receptor-hitmentioning
confidence: 99%
“…A good example is the transactivation of the EGFR by the AT 1 receptor, which mediates cell growth and survival, and has been implicated in numerous cardiovascular pathologies [ 42 ]. Using the Receptor-HIT assay in various immortalised and primary cells, we demonstrated AngII-induced recruitment of Grb2/Venus proximal to EGFR/Rluc8 and showed that the transactivation was independent of G q/11 and β-arrestin, and only partially dependent on EGFR tyrosine kinase activity [ 36 ]. We then followed up this study by investigating the involvement of a protein called TRIO in AT 1 -mediated EGFR transactivation, as it had previously been identified as an intermediate specific to AngII/AT 1 -mediated EGFR transactivation rather than EGF-mediated EGFR transactivation [ 43 ].…”
Section: Gpcr-other Receptor Receptor-hitmentioning
confidence: 99%
“…Moreover, it also mediates the generation of reactive oxygen species (ROS) [13] and the modulation of various ion channels [14][15][16]. The mechanisms underlying the AT1R-triggered regulation of tyrosine kinaserelated pathways are thought to initiate from (1) the de novo synthesis of cytokine and growth factor ligands, and/or (2) the binding of the AT1R with the upstream activators and scaffolds [17], (3) and/or the transactivation of growth factor receptors such as the epidermal growth factor receptor (EGFR) [18]. EGFR transactivation involves the capacity of GPCRs to activate metalloproteinases (MMPs) that cleave cell surface precursors of the EGF ligands, yielding the shed mature ligand that subsequently binds and activates the EGFR to pioneer various cellular signals [19], which are crucial for Ang II/AT1R-mediated hypertrophy and/ or proliferation of cardiac, vascular and renal cells.…”
Section: Introductionmentioning
confidence: 99%